Fate and Effects of Oil Pollutants in Extremely Cold Marine Environment. - Atlas,Ronald M. (1975)
The biodegradability of Prudhoe crude oil in the Arctic was studied in flow-through chemostats. Oil biodegradation was enhanced by addition of nitrogen and phosphorus. Enhancement of biodegradation was greater for an oleophilic fertilizer than a water-soluble fertilizer, even with repeated addition of the soluble fertilizer. In addition to Prudhoe crude, Arctic Diesel and JP5, as well as fractions of Prudhoe crude and individual hydrocarbons, were shown to be subject to biodegradation at low temperature by microorganisms indigenous to Arctic water and sediment, providing nitrogen and phosphorus were also added. No evidence, however, was obtained for biodegradation of Prudhoe crude oil spilled over or under sea ice. Contamination with crude oil or exposure to SO2 were found to inhibit essential algal and lichen metabolic functions. Natural gas was not inhibitory to these same organisms. Prudhoe crude oil and Arctic Diesel were found to be toxic to Arctic amphipods. The toxicity appears to be associated to a greater degree with the paraffinic fraction than with the aromatic or asphaltic fractions.